Syahz Ziaz Trading Online Store Management System - Norhamizan, Raudhah Syazwana; Nayef Abdulwahab Mohammed Alduais (Applied Information Technology And Computer Science, 2026)
The Syahz Ziaz Trading Online Store Management System was created in response to the inefficiencies of manual processes in handling goods sales. A completely functional web-based e-commerce platform designed for small enterprises that specialize in Sawanah Koko items is presented by this completed project, which was carried out under PSM2. Modules for customer registration, product catalog, order and inventory management, stock alerts, safe payment integration, and report production are all part of the system. The system was created following the Agile technique and included PHP, MySQL, HTML, CSS, and JavaScript. The outcomes of the tests demonstrated increased customer satisfaction, inventory tracking, and order accuracy. To improve accessibility and user experience, future improvements can include mobile optimization and more payment choices.